RUNX1B Expression Is Highly Heterogeneous and Distinguishes Megakaryocytic and Erythroid Lineage Fate in Adult Mouse Hematopoiesis. - Julia E Draper; Patrycja Sroczynska; Olga Tsoulaki; Hui Sun Leong; Muhammad Z H Fadlullah; Crispin Miller; Valerie Kouskoff; Georges Lacaud (PLoS Genetics)
The Core Binding Factor (CBF) protein RUNX1 is a master regulator of definitive hematopoiesis, crucial for hematopoietic stem cell (HSC) emergence during ontogeny. RUNX1 also plays vital roles in adult mice, in regulating the correct specification of numerous blood lineages. Akin to the other mammalian Runx genes, Runx1 has two promoters P1 (distal) and P2 (proximal) which generate distinct protein isoforms. The activities and specific relevance of these two promoters in adult hematopoiesis remain to be fully elucidated. Utilizing a dual reporter mouse model we demonstrate that the distal P1 promoter is broadly active in adult hematopoietic stem and progenitor cell (HSPC) populations. By contrast the activity of the proximal P2 promoter is more restricted and its upregulation, in both the immature Lineage- Sca1high cKithigh (LSK) and bipotential Pre-Megakaryocytic/Erythroid Progenitor (PreMegE) populations, coincides with a loss of erythroid (Ery) specification. Accordingly the PreMegE population can be prospectively separated into "pro-erythroid" and "pro-megakaryocyte" populations based on Runx1 P2 activity. Comparative gene expression analyses between Runx1 P2+ and P2- populations indicated that levels of CD34 expression could substitute for P2 activity to distinguish these two cell populations in wild type (WT) bone marrow (BM). Prospective isolation of these two populations will enable the further investigation of molecular mechanisms involved in megakaryocytic/erythroid (Mk/Ery) cell fate decisions. Having characterized the extensive activity of P1, we utilized a P1-GFP homozygous mouse model to analyze the impact of the complete absence of Runx1 P1 expression in adult mice and observed strong defects in the T cell lineage. Finally, we investigated how the leukemic fusion protein AML1-ETO9a might influence Runx1 promoter usage. Short-term AML1-ETO9a induction in BM resulted in preferential P2 upregulation, suggesting its expression may be important to establish a pre-leukemic environment.